Self-Reported Flow in Online Learning Environments for Teacher Education: A Quasi-Experimental Study Using a Counterbalanced Design - Lionel Alvarez; Romaine Carrupt; Catherine Audrin; Philippe Gay (MDPI AG, 2022)
Digitization in teacher education is currently being promoted, but the choice between face-to-face instruction and online learning environments remains challenging. Previous studies have documented ambivalent results regarding personal preference and academic achievement, and experimental investigations into attention comparing learning in these two settings are largely lacking. In this context, the present study adopts a counterbalanced design to compare different dimensions of student experience of flow in face-to-face settings and online learning environments. Two groups of students in teacher-training programs (n = 37) completed an EduFlow questionnaire at the end of the same interactive courses in the two different settings. The results indicate globally lower attention and engagement in the online environment, suggesting that in-person instruction induces better cognitive absorption, greater time transformation, and a stronger autotelic experience. While the findings represent a contribution to the discussion on how to best design online education, more research is needed to identify the specific mechanisms regarding attention and motivation that can impact flow in these two environments.